Isochoric freezing for the improvement of safety and quality of ready-to-eat hard-boiled eggs - Sumeyye Atci; Valerie S. McGraw; Matthew J. Powell-Palm; Tara McHugh; Boris Rubinsky; Cristina Bilbao-Sainz (Food Control, 2026)

Isochoric supercooling improves preservation of hepatic spheroid viability and structure compared to 4°C cold storage - Marie L. Dicker; Anthony N. Consiglio; Yun Weng; Juan C. Reyna; Brenda A.A.B. Ametepe; Tuan-Thinh Tong; Boris Rubinsky; Tammy T. Chang (Cryobiology, 2026)

Non-thermal isochoric freezing and brine retention: Quality and microbial safety of ready-to-eat hard-boiled eggs - Sumeyye Atci; Cristina Bilbao-Sainz; Valerie S. McGraw; Matthew J. Powell-Palm; Tara McHugh; Boris Rubinsky (International Journal of Food Microbiology, 2026)

In memoriam Kenneth B. Storey – Cryobiologist - Shannon N. Tessier; Boris Rubinsky; John G. Baust; Jennifer E. Storey (Cryobiology, 2026)

Pressure-activated disassembly of cryoprotectant supramolecules in isochoric freezing - Boris Rubinsky (Cryobiology, 2026)

Thermodynamic analysis of a partial freezing organ preservation protocol - Anthony N. Consiglio; Boris Rubinsky; Matthew J. Powell-Palm (Cryobiology, 2026)

Coaxial temperature controlled cryoprinting: A biomimetic technology inspired by the freezing survival mechanisms of the frog Rana sylvatica - Leo Lou; Linnea Warburton; Cristina Bilbao-Sainz; Nicholas Jean; Boris Rubinsky (Cryobiology, 2026)

The biomedical engineer’s pledge: overview and context - Antoni Ivorra; Txetxu Ausín; Laura Becerra-Fajardo; Antonio J. del Ama; Jesús Minguillón; Aracelys García-Moreno; Jordi Aguiló; Filipe Oliveira Barroso; Bart Bijnens; Oscar Camara; Sara Capdevila; Roger Castellanos Fernandez; et al. (Medical & Biological Engineering & Computing, 2026)
Although biomedical engineering (BME) is a profession with ethical responsibilities comparable to those in medicine, it has, until now, lacked a counterpart to the Hippocratic Oath. While professional societies have established codes of ethics for biomedical engineers, these documents lack the symbolic and ceremonial significance of an oath or pledge. By contrast, the recitation of the Hippocratic Oath, or its modern version, the “Physician’s Pledge,” serves as a powerful rite of passage for medical students, fostering a strong sense of ethical duty at the start of their professional journey. However, the content of the Hippocratic Oath includes elements specific to clinical practice and is not directly applicable to biomedical engineering. To fill this gap, we have created a “Biomedical Engineer’s Pledge,” comprising a preamble, ten promises, and a concluding statement, to inspire ethical awareness and establish a meaningful graduation tradition. Graphical abstract

Engineering novel systems to expand neural cryopreservation in supercooled conditions - Maxwell Johnson; Anthony N. Consiglio; Vivian Cormany; Boris Rubinsky (Cryobiology, 2025)

Cryobinding – A freezing assembly technology for tissue engineering - Leo (Tao) Lou; Boris Rubinsky (Cryobiology, 2025)

Influence of high hydrostatic pressure on ice nucleation - Anthony N. Consiglio; Boris Rubinsky (Cryobiology, 2025)

Isochoric freezing: Optimizing food preservation through controlled temperature and pressure conditions - Alan L. Maida; Anthony N. Consiglio; Cristina Bilbao-Sainz; Andrew Karman; Gary Takeoka; Matthew J. Powell-Palm; Boris Rubinsky (Cryobiology, 2025)

Studying isochoric supercooling (ISC) with new approach methodologies (NAMs) of the human heart - Jazmin I. Velazquez; Yongdeok Kim; Anthony N. Consiglio; Boris Rubinsky; Kevin E. Healy (Cryobiology, 2025)

Impact of storage temperature on the physicochemical properties and stability of oil-in-water emulsions under subzero isochoric cooling and conventional isobaric freezing - Sumeyye Atci; Cristina Bilbao-Sainz; Valerie S. McGraw; Tina Williams; Delilah Wood; Tara McHugh; Boris Rubinsky (Innovative Food Science & Emerging Technologies, 2025)

Investigating the effects of freezing temperature and oil content on the physiochemical characteristics and stability of oil-in-water emulsions under isochoric freezing conditions - Sumeyye Atci; Cristina Bilbao-Sainz; Valerie S. McGraw; Delilah Wood; Tara McHugh; Boris Rubinsky (Food Research International, 2025)

The thermodynamic principles of isochoric freezing pressure-aided supercooling - Alan L. Maida; Pedro Alejandro Perez; Cristina Bilbao-Sainz; Boris Rubinsky; Anthony N. Consiglio (Cryobiology, 2025)

The inactivation of Shiga toxin-producing Escherichia coli (STEC) and Listeria monocytogenes using isochoric freezing in raw milk and carrot juice - Alison Lacombe; Beatrice L. Harvey; Jared Van Blair; Natalie Chapman; Cristina Bilbao-Sainz; Tara McHugh; Boris Rubinsky; Vivian C.H. Wu (Food Control, 2025)

Isochoric freezing of raw cow milk: Enhancing storage and nutritional stability in perishable foods - Alan L. Maida; Cristina Bilbao-Sainz; Andrew Karman; Gary Takeoka; Matthew J. Powell-Palm; Boris Rubinsky (Cryobiology, 2024)

Application of photon counting X-ray computed tomography to the study of vitrification in cryopreservation solutions - Anthony N. Consiglio; Alaa M. Ali; Brooke Chang; Gala Sanchez van Moer; Jason T. Parker; Matthew J. Powell-Palm; Boris Rubinsky; Simo A. Mäkiharju (Cryobiology, 2024)

Cryopreservation of 3D bioprinted scaffolds with temperature-controlled-cryoprinting - Linnea Warburton; Boris Rubinsky (Cryobiology, 2024)

Preservation of food by isochoric (Constant volume) freezing - Cristina Bilbao-Sainz; Boris Rubinsky; Vivian C.H. Wu; Tara McHugh (Cryobiology, 2024)

Experimental observation of cavity-free ice-free isochoric vitrification via combined pressure measurements and photon counting x-ray computed tomography - Alaa M. Ali; Brooke Chang; Anthony N. Consiglio; Gala Sanchez Van Moer; Matthew J. Powell-Palm; Boris Rubinsky; Simo A. Mäkiharju (Cryobiology, 2024)

Inactivation of Bacillus cereus spores by isochoric freezing - Chenang Lyu; Guangda Luo; Ran An; Dapeng Wang; Boris Rubinsky (Food Control, 2024)

Calcium impregnation during isochoric cold storage to improve postharvest preservation of fresh blueberries - Cristina Bilbao-Sainz; Angéle Millé; Bor-Sen Chiou; Gary Takeoka; Boris Rubinsky; Tara McHugh (Postharvest Biology and Technology, 2024)

Direct comparison of isobaric and isochoric vitrification of two aqueous solutions with photon counting X-ray computed tomography - Jason T. Parker; Anthony N. Consiglio; Boris Rubinsky; Simo A. Mäkiharju (Cryobiology, 2024)

Cryopreservation of coral microfragments - Emmett Michael Henley; Matthew J. Powell-Palm; Anthony N. Consiglio; Claire Lager; Brooke Chang; Riley Perry; Kendall Fitzgerald; Jonathan Daly; Boris Rubinsky; Mary Hagedorn (Cryobiology, 2023)

Extreme value statistics for estimating the freezing probability of supercooled water - Anthony N. Consiglio; Yu Ouyang; Matthew J. Powell-Palm; Boris Rubinsky (Cryobiology, 2023)

Response to “‘Isochoric freezing’: Ambitions and reality” - Matthew J. Powell-Palm; Boris Rubinsky (Journal of Food Engineering, 2023)

Temperature controlled cryoprinting of food for dysphagia patients - Leo Lou; Cristina Bilbao-Sainz; Delilah Wood; Boris Rubinsky (Innovative Food Science & Emerging Technologies, 2023)

Preservation of Tilapia ( Oreochromis aureus ) Fillet by Isochoric (Constant Volume) Freezing - Cristina Bilbao-Sainz; Amanda J. G. Sinrod; Tina Williams; Delilah Wood; Bor-Sen Chiou; David F. Bridges; Vivian C. H. Wu; Chenang Lyu; Boris Rubinsky; Tara McHugh (Journal of Aquatic Food Product Technology, 2020)

A Conceivable Mechanism Responsible for the Synergy of High and Low Voltage Irreversible Electroporation Pulses - Yanpeng Lv; Chenguo Yao; Boris Rubinsky (Annals of Biomedical Engineering, 2019)

Tissue Ablation by a Synergistic Combination of Electroporation and Electrolysis Delivered by a Single Pulse - Mary Phillips; Hanush Krishnan; Narayan Raju; Boris Rubinsky (Annals of Biomedical Engineering, 2016)

Magnetic Resonance Imaging Characteristics of Nonthermal Irreversible Electroporation in Vegetable Tissue - Mohammad Hjouj; Boris Rubinsky (The Journal of Membrane Biology, 2010)

Irreversible Electroporation for Microbial Control of Drugs in Solution - Alex Golberg; Michael Belkin; Boris Rubinsky (AAPS PharmSciTech, 2009)